Hyperhomocysteinemia and pregnancy outcomes in women with polycystic ovary syndrome: A case-control study - Elene Asanidze; Jenaro Kristesashvili; Nino Parunashvili; Manana Urjumelashvili; Zurab Tsetskhladze; Aleksandre Asanidze (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: One of the reproductive medicine challenges is to determine the role of hyperhomocysteinemia in the pathogenesis of polycystic ovary syndrome (PCOS), especially in women with recurrent pregnancy loss (RPL). Objective: Determine the correlation between hyperhomocysteinemia and pregnancy outcome in women with PCOS. Materials and Methods: This case-control study involved 245 women (20-30 yr) and was conducted in Georgia, Tbilisi from 2019-2022. Of these, 175 were women with PCOS (study group) and 70 were healthy women (control group). Women with PCOS were divided into group I with RPL (n = 90), and group II with live births (n = 85). Group I was divided into subgroups A and B with and without insulin resistance. The investigation measured homocysteine (Hcy), follicle-stimulating, luteinizing, anti-Mullerian hormones, total and free testosterone were determined. To determine the ovarian volume and antral follicle count, participants also underwent an ultrasound examination. Results: In women with PCOS, the average Hcy level was significantly higher than in the controls, p < 0.05. In group I, the average Hcy level was significantly higher than in group II and controls, p < 0.05. There was no significant difference in average Hcy level between group II and controls. The average Hcy level in group I, subgroup A was significantly higher than in subgroup B, p < 0.05. The average total, free testosterone levels, and homeostatic model assessment-insulin resistance levels (HOMA-IR) in group I was significantly higher than in group II and controls. HOMA-IR in group II and controls did not differ significantly. The average anti-Mullerian hormone levels in women with PCOS were significantly higher than controls, p < 0.05. No significant difference was observed in average anti-Mullerian hormone level, ovarian volume, antral follicle count, and body mass index between the comparison groups of PCOS. In group I, a positive correlation between Hcy with HOMA-IR was detected. Conclusion: Serum Hcy levels are elevated in women with PCOS and RPL, which correlates with their insulin resistance status.